Isofagomine In Vivo Effects in a Neuronopathic Gaucher Disease Mouse - Sun, Ying; Ran, Huimin; Liou, Benjamin; Quinn, Brian; Zamzow, Matt; Zhang, Wujuan; Bielawski, Jacek; Kitatani, Kazuyuki; Setchell, Kenneth D. R.; Hannun, Yusuf A.; Grabowski, Gregory A. (PloS one, 2011)
The pharmacological chaperone, isofagomine (IFG), enhances acid β-glucosidase (GCase) function by altering folding, trafficking, and activity in wild-type and Gaucher disease fibroblasts. The in vivo effects of IFG on GCase activity, its substrate levels, and phenotype were evaluated using a neuronopathic Gaucher disease mouse model, 4L;C* (V394L/V394L + saposin C-/-) that has CNS accumulation of glucosylceramide (GC) and glucosylsphingosine (GS) as well as progressive neurological deterioration. IFG administration to 4L;C* mice at 20 or 600 mg/kg/day resulted in life span extensions of 10 or 20 days, respectively, and increases in GCase activity and protein levels in the brain and visceral tissues. Cerebral cortical GC and GS levels showed no significant reductions with IFG treatment. Increases of GC or GS levels were detected in the visceral tissues of IFG treated (600 mg/kg/day) mice. The attenuations of brain proinflammatory responses in the treated mice were evidenced by reductions in astrogliosis and microglial cell activation, and decreased p38 phosphorylation and TNFα levels. Terminally, axonal degeneration was present in the brain and spinal cord from untreated and treated 4L;C* mice. These data demonstrate that IFG exerts in vivo effects by enhancing V394L GCase protein and activity levels, and in mediating suppression of proinflammation, which led to delayed onset of neurological disease and extension of the life span of 4L;C* mice. However, this was not correlated with a reduction in the accumulation of lipid substrates.